ANALISIS MOTIVASI KERJA KARYAWAN FRONT OFFICE HOTEL RESTY MENARA PEKANBARU - Saputra, Yadi; Achnes, Syofia; Rifiyan, Andi M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research aimed about front office employee’s motivation at Resty Menara HotelPekanbaru. This research aims to: (1) to knows about front office employee’s motivation atResty Menara Hotel Pekanbaru. (2) To know the multi ways to increase front officeemployee’s motivation at Resty Menara Hotel Pekanbaru.The sample used in this research was 8 people. This research using descriptivemethods to examine the issues presented in this research.The results of this research indicate that based on the research results obtained on themotivation of the front office employee at Resty Menara Hotel pekanbaru could be quitegood. This is evidenced by the acquisition of the overall total score of hygiene factor andmotivator factor, which is 191 points.Keyword: Motivation, employee, hygiene factor, motivator factor.